Daily chlorproguanil is an effective alternative to daily proguanil in the prevention of Plasmodium falciparum malaria in Kenya - Nevill, C. G.; Lury, J. D.; Mosobo, M. K.; Watkins, H. M.; Watkins, W. M. (Transitional of the Royal Society of Tropical Medicine and Hygiene)
To test the efficacy of chlorproguanil prophylaxis, 156 malaria-free schoolchildren in the coastal region of Kenya were allocated at random to receive either 7.5 mg chlorproguanil daily, 50 mg chlorproguanil weekly, 100 mg proguanil daily, or 100 mg calcium lactate weekly (placebo). The children were followed up daily for 169 d, by which time Plasmodium falciparum parasitaemia had occurred in 92% of the placebo group, 3 1% of the daily proguanil group, 38% of the daily chlorproguanil group and 55% of the weekly chlorproguanil group. There was significant reduction (P<O.OOl) in the risk of parasitaemia in all the groups receiving chemoprophylaxis. Daily chlorprognanil and daily proguanil were equally effective, and significantly more effective than weekly high dose chlorproguanil. No significant toxicity was reported or observed. Thus daily chlorproguanil20 mgi60 kg is a cheap and effective alternative to proguanil for chemoprophylaxis.
Keywords: Prophylaxis; Malaria; Placebo; Toxicity; Chemoprophylaxis; Kenya